Shifts in the Human Gut Microbiota Structure Caused by Quadruple Helicobacter pylori Eradication Therapy - Olekhnovich, Evgenii I.; Manolov, Alexander I.; Samoilov, Andrey E.; Prianichnikov, Nikita A.; Malakhova, Maja V.; Tyakht, Alexander V.; Pavlenko, Alexander V.; Babenko, Vlad V.; Larin, Andrey K.; Kovarsky, Boris A.; Starikova, Elizaveta V.; Glushchenko, Oksana E.; et al. (Frontiers in Microbiology, 2019)
Human gut microbiome plays an important role both in health and disease. Use of antibiotics can alter gut microbiota composition, which leads to various deleterious events. Here we report a whole genome sequencing metagenomic/genomic study of the intestinal microbiota changes caused by Helicobacter pylori (HP) eradication therapy. The analyzed dataset included 80 gut metagenomes from 40 patients before and after HP eradication obtained by SOLiD 5500W technology, the 10 ones from 4 patients obtained by Illumina HiSeq 2500 and 19 genomes of Enterococcus spp. recovered from those patients and also sequenced by Illumina HiSeq 2500. Using new approaches for metagenomic data analysis we revealed the statistically significant decrease in taxonomic alpha-diversity and relative abundance of Bifidobacterium adolescentis species after HP eradication therapy, whereas those of Enterococcus faecium were increased. We detected the changes in the general metagenome resistome profiles as well: after HP eradication therapy the ermB, CFX group and tetQ genes were overrepresented, the tetO and tetW genes were underrepresented. We confirmed these results with genome-resolved metagenomic (GRM) approaches. The MAGs (metagenome-assembled genomes) abundance profiles changed dramatically after HP eradication therapy. With focus on ermB gene conferring the resistance to macrolides, included into HP eradication therapy sheme, we showed links between antibiotic resistance genes (ARGs) and MAGs. The local assembly of ermB gene metagenomic context showed the presence of this gene both in Enterococcus faecalis and Bacteroides dorei MAGs (the ones that increased after HP eradication therapy) and its co-localization with multiple ARGs (including tetQ). The co-localization in one mobile genetic element or genome may be associated with the increase of tetQ relative abundance after HP eradication therapy. Moreover some E. faecium strains isolated from stool samples after HP eradication therapy revealed the greater antibiotic resistance in vitro in comparison with others isotates, as well as the number of ARGs conferring resistance to macrolides and tetracyclines. Thus, HP eradication causes multiple shifts and alterations of the intestinal microbiota and leads to the ARGs accumulation.